2014
DOI: 10.1186/1475-2859-13-79
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and RRR-α-tocopherol production in Stichococcus bacillaris strain siva2011 in a balloon bioreactor

Abstract: BackgroundGreen microalgae represent a renewable natural source of vitamin E. Its most bioactive form is the naturally occurring RRR-α-tocopherol which is biosynthesized in photosynthetic organisms as a single stereoisomer. It is noteworthy that the natural and synthetic α-tocopherols are different biomolecular entities. This article focuses on RRR-α-tocopherol production in Stichococcus bacillaris strain siva2011 biomass in a bioreactor culture with methyl jasmonate (MeJa) elicitor. Additionally, a nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Among the tested algae, 37 were aeroterrestrial and some of them contained high amounts (up to 1062.02 µg g −1 dm) of α-tocopherol: the green Bracteacoccus sp., Coccomyxa sp., Muriella terrestris, Stichococcus bacillaris, yellow-green Botrydiopsis intercedens, Heterococcus sp., Xanthonema sp., eustigmatophycean Monodus guttula, etc. Currently, the most bioactive form of vitamin E-the naturally occurring RRR-α-tocopherol-was discovered in Stichococcus bacillaris [76]. Considering the worldwide distribution of this aeroterrestrial filamentous alga [53], we note it as important potential renewable natural source of vitamin E. Two cryophilic species of green algae-Chlamydocapsa sp.…”
Section: Algae In Skincare With Special Attention To Sunscreen and Anmentioning
confidence: 99%
“…Among the tested algae, 37 were aeroterrestrial and some of them contained high amounts (up to 1062.02 µg g −1 dm) of α-tocopherol: the green Bracteacoccus sp., Coccomyxa sp., Muriella terrestris, Stichococcus bacillaris, yellow-green Botrydiopsis intercedens, Heterococcus sp., Xanthonema sp., eustigmatophycean Monodus guttula, etc. Currently, the most bioactive form of vitamin E-the naturally occurring RRR-α-tocopherol-was discovered in Stichococcus bacillaris [76]. Considering the worldwide distribution of this aeroterrestrial filamentous alga [53], we note it as important potential renewable natural source of vitamin E. Two cryophilic species of green algae-Chlamydocapsa sp.…”
Section: Algae In Skincare With Special Attention To Sunscreen and Anmentioning
confidence: 99%
“…Among them, the α-tocopherol production of Chlorophyta was higher than that of Rhodophyta, which could be a natural source of α-tocopherol ( Mudimu et al, 2017 ). Sivakumar et al (2014) discovered a new strain ( Stichococcus bacillaris strain siva2011) that produces natural RRR-α-tocopherol and could be commercialized. Leya et al (2009) found two strains of Raphidonema from snow and permafrost substrates, which were good α-tocopherol producers ( Leya et al, 2009 ).…”
Section: Sunscreenmentioning
confidence: 99%
“…植物中生育酚合成的关键前体PDP主要来源 于叶绿素的降解和循环利用 [13,19] , 但参与叶绿素降解 . 在裂丝藻中添加茉莉酸甲 酯作为诱导剂来调节与藻类应激胁迫相关的基因表达 也可以增加特定异构体的生育酚的产量 [25] . 但藻类特 殊的培养条件限制了它的工业应用.…”
Section: 通过过表达Hppd来增加游离hga的积累对于生育三unclassified